2017
DOI: 10.2215/cjn.06600616
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hypertension among First-Time Symptomatic Kidney Stone Formers

Abstract: The risk of hypertension was higher after the first symptomatic kidney stone event. However, kidney stone severity, type, and treatment did not associate with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 35 publications
(41 reference statements)
3
32
0
Order By: Relevance
“…Hypertension was a metabolic syndrome parameter that has been common knowledge was associated with risk of kidney stones (Rendina et al, 2009;Jung et al, 2011). Hypertension was common in many patients with kidney stones formers (Kittanamongkolchai et al, 2017). This study also showed that hypertension was associated with the risk of kidney stones in male and female respondents.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Hypertension was a metabolic syndrome parameter that has been common knowledge was associated with risk of kidney stones (Rendina et al, 2009;Jung et al, 2011). Hypertension was common in many patients with kidney stones formers (Kittanamongkolchai et al, 2017). This study also showed that hypertension was associated with the risk of kidney stones in male and female respondents.…”
Section: Resultssupporting
confidence: 58%
“…Screening test study at a health promotion center in Seoul, Korea (116,536 respondents) reported that hypertension was a significantly related factor to the presence of kidney stones (male; OR 1.08; 95% CI 1.01-1.15; p=0.043, female; OR 1.24; 95% CI 1.08-1.42; p=0.002) (Kim et al, 2013). A cross sectional study in Texas reported that hypertension was identified as a significant risk factor associated with kidney stones (Hazard Ratio=1.50; 95% confidence (Kittanamongkolchai et al, 2017). Other studies reported that hypertension is associated with hypercalciuria (Ferraro et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Although risk factors, such as diet, hydration, and urine composition, have long been associated with stone risk, epidemiologic studies have linked nephrolithiasis with common systemic conditions, such as metabolic syndrome and cardiovascular disease (3)(4)(5). A history of nephrolithiasis increases the risk of hypertension and diabetes mellitus (6)(7)(8). There are sex-specific differences in both risk factors and complications of stone disease (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Since the association between arterial hypertension and nephrolithiasis was described in 1965 for the first time by Tibblin [ 4 ], much effort has been devoted to this field. Data from several observational studies suggested a risk of hypertension in nephrolithiasis patients of 1.24–1.96 compared to the general population [ 5 11 ]. A previous review performed by Cupisti et al [ 12 ] has shown the current understanding of the potential link between nephrolithiasis and the occurrence of hypertension, but no meta-analysis has been used to examine the relationship.…”
Section: Introductionmentioning
confidence: 99%